Prevalence of IgG e IgM antibodies against COVID-19 in essential municipal personnel. Ushuaia, T. del Fuego, Argentina (Actualizaciones en Sida e Infectología, 2021)
With the purpose of expanding epidemiological knowledge about the circulation of SARS-CoV-2 in the city of Ushuaia during the outbreak that occurred from March to May of this current, we plan to carry out an observational, cross-sectional study from May to July, seeking the serological response to contact with the virus in essential municipal workers. N = 1316. The data were entered into a platform with restricted entry, to later cross the variables obtained in Excel format. Most of the people studied were male, with a mean age of 38 years. 20% of the people with IgG + had an epidemiological link. The prevalence was 2.88%. Those who presented IgM+ were discarded by another method, being considered false positives. The early idea and implementation of the study was useful to evaluate asymptomatic viral shedding in municipal personnel affected by essential tasks and to make decisions in the early stages of the pandemic. No significant differences were found in the most exposed groups. Cases of asymptomatic interfamily transmission were observed. These serological tests do not have diagnostic purposes nor do they confer an immune passport. We were able to establish the reliability of the technique used, mainly in relation to IgG. The method was optimized. We believe that public policies based on scientific evidence allow us to make better decisions for the benefit of the community. We believe that the present study contributes to the state of understanding in the matter. Each report can be useful for understanding viral shedding.
Keywords: SARS-CoV-2; cross-sectional serological study; essential workers; epidemiological investigation